Solar drying of wastewater sludge: a case study in Marrakesh, Morocco. Issue 10 (29th April 2019) - Belloulid, Mohamed Oussama; Hamdi, Hassan; Mandi, Laila; Ouazzani, Naaila
ABSTRACT: This paper presents a site-specific study of solar drying of wastewater sludge in the region of Marrakesh in Morocco. During the course of the experiments, drying pans (DP) and solar greenhouse drying processes were studied in summer and winter seasons. To simulate the DP process, representative samples were dried in plastic cylindrical plates in ambient conditions, near an Open Greenhouse Sludge Dryer (OGSD) designed and constructed as a tunnel plant. Results showed that the dry solids' (DS) concentration of 80% was reached in only 32 h in summer and 57 h in winter by DP process. The OGSD reached the same concentration in 45 and 65 h in summer and winter, respectively. The important influence of wind speed had a greater effect than the temperature on drying rate. The sludge water evaporation caused a large volume reduction during DP and OGSD processes in both seasons. The removal of total and fecal coliforms during summer experiment was noticeably better in the OGSD, even for Clostridium perfringens . Based on the obtained results, the solar greenhouse drying was practical and beneficial to wastewater sludge management and can be recommended as an alternative to DP in arid climate zones generally, and in Marrakesh particularly.